Antioxidant and anti-inflammatory activity of fruit, leaf and branch extracts of Paliurus spina-christi P. Mill. - ŞEN, ALİ (MARMARA UNIV, FAC PHARMACY, 2018)
In this study, it is aimed to investigate antioxidant and anti-inflammatory activities of ethanol extracts and their n-hexane, chloroform, ethylacetate, and aqueous ethanol fractions of the fruits, leaves, and branches of Paliurus spinachristi P. Mill. (Rhamnaceae). The antioxidant activity of the extracts was tested by DPPH and ABTS methods and the results were expressed as IC50 values. The total phenolic content was determined by Folin-Ciocalteu method and the results were expressed as mg of gallic acid equivalent per g dry extract. Anti-inflammatory activity of extracts were evaluated against 5-lipoxygenase enzyme. In particular, all extracts obtained from branches of P. spina-christi, except hexane extract, showed strong antioxidant activity against DPPH and ABTS radicals. Ethyl acetate and ethanol extracts of branches of P. spina-christi showed the highest antioxidant activity in DPPH and ABTS assays with IC50 values of 15.54 and 22.06 mu g/ml, respectively. Also, the highest total phenol content was found in the ethylacetate extract of branches of P. spina-christi (286.6 mg/g). Ethyl acetate and ethanol extracts of leaves of P. spina-christi with IC50 values of 66.28 and 76.75 j mu g/ml were found to have the best anti-inflammatory activity in the lipoxygenase (LOX) inhibition assay used to evaluate anti-inflammatory activities of extracts. These results demonstrate that ethanol and ethyl acetate extracts from branches and leaves of Paliurus spina-christi have significant antioxidant and anti-inflammatory activity. Also, these results confirm the folk use of the plant as an antiinflammatory medicine.
Keywords: Paliurus spina-christi P. Mill.; Rhamnaceae; Antioxidant activity; Anti-inflammatory activity; FOLK MEDICINAL-PLANTS; TURKEY; FLAVONOIDS; ISTANBUL; THORN